HUBUNGAN CITARASA MAKANAN DAN LAMA RAWAT INAP DENGAN SISA MAKANAN PASIEN DI RUMAH SAKIT - Putu Lika Septarini Dewi; Ida Ayu Eka Padmiari,SKM.,M.Kes; Ni Made Dewantari,SKM,M.FOr (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2023)
The taste of food is a taste that involves the sense of taste (tongue). The taste of food includes two main aspects, namely the appearance of the food when it is served and the taste of the food when it is eaten. Inpatient services are a group of health services found in hospitals which are a combination of several service functions. The length of hospitalization indicates the number of days a patient has been hospitalized. Food waste is food waste is the volume or percentage of food that is not consumed and is disposed of as waste and can be used to measure the effectiveness of the menu. One indicator of the success of a hospital meal is related to the patient's leftovers. This study aims to determine the relationship between food taste and length of stay with the patient's leftover food at the hospital. The method used is the method of literature review.Research results from the results of the analysis of the literature there are 2 articles that discuss the taste of food stating the average taste of good food is an average of 60%. There are 2 articles that explain the length of hospitalization with different categories, namely the length of stay with the old category as much as 7.3%, stating the length of days of hospitalization with the category of 4 days as much as 67%. Based on 4 articles about leftovers, it is quite diverse according to individual needs and most of the samples left a lot of food. The conclusion of the 8 journals concluded that based on the results of a literature review on food taste, it was known that most of the samples were in the good category. Regarding the length of hospitalization, it was explained that some of the results of the length of stay in each article varied according to the provisions of the length of hospital stay. Regarding leftovers, it is known that most of the samples still left food served by the hospital. The relationship between food taste and patient leftovers at the hospital, most of the articles said that there was a significant relationship between food taste and patient leftovers. The relationship between length of stay and food waste of patients at the hospital, that there was a significant relationship between length of stay and food waste of patients and some stated that there was no relationship between length of stay and food waste.Keywords: Keywords: leftovers, taste of food, length of hospitalization